Interbody fusion cage with piezoelectric property on surface and preparation method of interbody fusion cage

The titanium alloy intervertebral fusion device is produced through 3D printing process and a piezoelectric ceramic coating is formed on its surface, which solves the problems of high elastic modulus of existing intervertebral fusion device materials and the surface is not conducive to bone integration, achieving better bone integration and fusion effects.

CN119791916APending Publication Date: 2025-04-11GUANGZHOU FIRST PEOPLES HOSPITAL (GUANGZHOU DIGESTIVE DISEASE CENT GUANGZHOU FIRST PEOPLES HOSPITAL GUANGZHOU MEDICAL UNIV THE SECOND AFFILIATED HOSPITAL OF SOUTH CHINA UNIV OF TECH) +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510059913.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The metal material of existing intervertebral fusion devices has a high elastic modulus, which leads to sinking and stress occlusion of the fusion device. The surface of non-metallic materials such as PEEK is smooth and there are fewer hydrophilic groups, which affects bone integration.

Method used

A 3D printing process is used to make an intervertebral fusion device of titanium alloy material and a piezoelectric ceramic coating is formed on its surface, which improves the mechanical properties and biocompatibility of the material through heat treatment and spraying processes.

Benefits of technology

It improves the mechanical properties and biocompatibility of intervertebral fusion devices, stimulates tissue growth and repair, accelerates bone integration, and promotes intervertebral fusion in the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119791916A_ABST
    Figure CN119791916A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical instruments, and discloses an interbody fusion cage with a piezoelectric property on the surface and a preparation method thereof, and the preparation method comprises the following steps: S1, printing a sample of the interbody fusion cage by adopting a 3D printing process; s2, the sample in the step S1 is subjected to heat treatment, the heat treatment temperature is 800 DEG C, and the heat treatment time is a first duration; and S3, coating the piezoelectric ceramic powder on the surface of the sample to form a piezoelectric coating. The interbody fusion cage sample is manufactured by adopting a 3D printing process, is simple and convenient to form and can be customized according to the requirements of different patients; heat treatment is carried out after the sample is manufactured and formed, an alpha + beta titanium alloy crystalline phase structure can be obtained, and the comprehensive performance of the sample is improved; the piezoelectric coating is formed on the surface of the sample, the interbody fusion cage has piezoelectricity, and the piezoelectric coating can stimulate tissue growth and repair, accelerate osseointegration and promote interbody fusion of the human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical devices, and in particular to an intervertebral fusion device with piezoelectric properties on the surface and a preparation method thereof. Background Art

[0002] In spinal fusion surgery, implants such as intervertebral fusion devices are needed to fuse and fix the damaged parts. Therefore, the demand for implants such as intervertebral fusion devices has also increased. Early intervertebral fusion devices were made of stainless steel. Now there are titanium alloy fusion devices and non-metallic fusion devices. Among them, non-metallic fusion devices are mainly polyetheretherketone (PEEK) intervertebral fusion devices.

[0003] The elastic modulus of existing metal intervertebral fusion devices is too high, and the main problems are sinking and stress shielding of the fusion device. The design of releasing trabecular bone structure can improve the bone integration effect to a certain extent, but it cannot change the inherent mechanical properties of the metal itself. Although PEEK fusion devices have reliable biocompatibility, stable chemistry, and excellent mechanical properties and elastic modulus, their surface is relatively smooth and has fewer hydrophilic groups, which cannot provide an ideal osteogenic environment for cell adhesion, which may lead to poor bone integration ability. There is a space for fibrous connective tissue between the bone and the fusion device, which affects bone fusion. Summary of the invention

[0004] The purpose of the present invention is to provide an intervertebral fusion device with piezoelectric properties on the surface, so as to improve the mechanical properties of the intervertebral fusion device, stimulate tissue growth and repair, and accelerate bone integration; the present invention also provides a method for preparing the intervertebral fusion device.

[0005] In order to achieve the above object, the present invention provides a method for preparing an intervertebral fusion cage, comprising the following steps:

[0006] S1, a sample of an intervertebral fusion cage was printed using 3D printing technology, and the sample material was titanium alloy;

[0007] S2, heat treating the sample in step S1, the heat treatment temperature is 800° C., and the heat treatment time is a first duration;

[0008] S3, coating the piezoelectric ceramic powder on the surface of the sample to form a piezoelectric coating.

[0009] Preferably, step S3 comprises:

[0010] S3.1, preheating the sample in a vacuum environment, the preheating temperature is 130℃-170℃, and the preheating time is the second time length;

[0011] S3.2, piezoelectric ceramic powder is sprayed onto the sample using a plasma arc spraying process;

[0012] S3.3, polarizing the sample in an oil bath, the oil bath temperature range is 40°C-70°C, and the polarization time is the third duration;

[0013] S3.4, clean the sample and obtain the intervertebral fusion cage.

[0014] Preferably, in step S3.1, preheating is performed in a vacuum oven at a preheating temperature of 150°C.

[0015] Preferably, the second duration is 10 minutes.

[0016] Preferably, in step S3.2, when plasma arc spraying is adopted, the spraying voltage range is 45-50V, the spraying current range is 500-550A, and the main gas flow range is 2300-2800ml / min.

[0017] Preferably, in step S3.3, the sample is polarized in a polarizer with an oil bath temperature of 70°C.

[0018] Preferably, the third duration is 30 minutes.

[0019] Preferably, in step S3.4, the sample is washed at least twice with anhydrous ethanol, with each washing lasting 5 minutes.

[0020] Preferably, in step S2, the first duration is 2 hours.

[0021] The present invention also provides an intervertebral fusion device having a surface with piezoelectric properties, which is prepared and formed using the preparation method of the intervertebral fusion device described in any of the above technical solutions. The intervertebral fusion device having a surface with piezoelectric properties includes a rear support segment and a plurality of front limbs connected to the rear support segment, the inner wall of each of the front limbs having an internal thread segment at one end away from the rear support segment, the outer wall of the front limb has an external thread segment, and the surfaces of the rear support segment and the front limbs both have a piezoelectric coating.

[0022] Compared with the prior art, the intervertebral fusion device having piezoelectric properties on the surface and the preparation method thereof in the embodiment of the present invention have the following beneficial effects: the intervertebral fusion device sample is manufactured by 3D printing technology, the molding is simple, and it can be customized according to the needs of different patients; the sample is heat treated after molding to obtain an α+β titanium alloy crystal phase structure, and the comprehensive performance of the sample is improved; a piezoelectric coating is formed on the surface of the sample, the intervertebral fusion device has piezoelectricity, and the piezoelectric coating can stimulate tissue growth and repair, accelerate bone integration, and promote intervertebral fusion in the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic flow chart of the method for preparing the intervertebral fusion cage of the present invention;

[0024] Figure 2 It is a schematic structural diagram of an intervertebral fusion device with piezoelectric properties on its surface according to the present invention;

[0025] Figure 3 yes Figure 2 A top view of an intervertebral fusion cage having a surface having piezoelectric properties;

[0026] Figure 4 yes Figure 2 Bottom view of an intervertebral fusion cage having a surface having piezoelectric properties.

[0027] In the figure, 1, rear supporting segment, 2, front limb, 3, internal thread segment, 4, external thread segment. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0029] A preferred embodiment of a method for preparing an intervertebral fusion cage according to the present invention is as follows: Figure 1 As shown, the following steps are included:

[0030] S1, a sample of an intervertebral fusion cage was printed using 3D printing technology, and the sample material was titanium alloy;

[0031] S2, heat treating the sample in step S1, the heat treatment temperature is 800° C., and the heat treatment time is a first duration;

[0032] S3, coating the piezoelectric ceramic powder on the surface of the sample to form a piezoelectric coating.

[0033] In step S1, the sample material is titanium alloy, which can improve the bone integration effect and has reliable biocompatibility, chemical and mechanical properties. The sample of the intervertebral fusion device is made by 3D printing technology. The molding method of 3D printing technology is simple. When the patient's condition is different, it can be customized according to the needs and is easy to use.

[0034] In this embodiment, the 3D printing process for making a sample of an intervertebral fusion cage includes the following steps:

[0035] S1.1, design a three-dimensional model of the intervertebral fusion cage using three-dimensional design software, and export the model file in STL format. Specifically, the three-dimensional design software can be general software such as 3D one Plus;

[0036] S1.2, import the STL format model file into the software on the 3D printer, set the printing parameters of the 3D printer, specifically, the printing parameters include laser power of 350-380kW, setting the printing layer thickness to 50um, scanning spacing to 90um, scanning speed to 1600mm / s, and save the model in gcode format after the printing parameters are set. Using high scanning speed and reasonable scanning spacing can improve printing efficiency and may improve the detail resolution of the part.

[0037] S1.3, generate support structure, preheat the substrate before forming the support structure, the preheating temperature is 200℃ to reduce thermal stress and warping of the material during printing, and start printing after nitrogen is introduced. The choice of nitrogen helps to reduce metal oxidation and improve the microstructure and performance of the product.

[0038] S1.4, after the sample is printed, remove the support structure using needle-nosed pliers.

[0039] In step S2, the sample is heat treated. High temperature post-treatment can obtain an α+β titanium alloy crystal phase structure, which helps to improve the uniformity and mechanical strength of the sample structure, thereby improving the overall performance of the sample.

[0040] In step S3, a piezoelectric coating is formed on the surface of the sample, and the piezoelectric coating can stimulate tissue growth and repair, promote intervertebral fusion, and prolong intervertebral fusion time. In this embodiment, the piezoelectric coating is made by thermal spraying technology. In this embodiment, the material of the piezoelectric ceramic coating is barium titanate or zinc oxide, and the coating thickness is 30-70 microns.

[0041] The sample of the preparation method of the intervertebral fusion device is made by 3D printing technology, which is easy to shape and can be customized according to the needs of different patients; the sample is heat treated after being formed to obtain an α+β titanium alloy crystal phase structure, and the comprehensive performance of the sample is improved; a piezoelectric coating is formed on the surface of the sample, and the intervertebral fusion device has piezoelectricity. The piezoelectric coating can stimulate tissue growth and repair, accelerate bone integration, and promote intervertebral fusion in the human body.

[0042] Preferably, step S3 comprises:

[0043] S3.1, preheating the sample in a vacuum environment, the preheating temperature is 130℃-170℃, and the preheating time is the second time length;

[0044] S3.2, piezoelectric ceramic powder is sprayed onto the sample using a plasma arc spraying process;

[0045] S3.3, polarizing the sample in an oil bath, the oil bath temperature range is 40°C-70°C, and the polarization time is the third duration;

[0046] S3.4, clean the sample and obtain the intervertebral fusion cage.

[0047] In step S3.1, preheating in a vacuum environment can prevent the sample temperature from being too low, so that the piezoelectric coating and the sample surface can be stably bonded. The preheating temperature is 130°C-170°C. Using low temperature preheating can save energy and reduce the derivative problems that may be caused by overheating.

[0048] In step S3.2, the plasma arc spraying process is a mature thermal spraying technology. The piezoelectric coating sprayed by the plasma arc spraying process is dense and has high bonding strength, so a piezoelectric coating with good performance can be obtained.

[0049] In step S3.3, the sample is placed in an oil bath so that the sample can obtain piezoelectric properties. In this embodiment, the oil bath temperature ranges from 40°C to 70°C. A low-temperature oil bath is used, and the polarization performance is more stable.

[0050] Preferably, in step S3.1, preheating is performed in a vacuum oven at a preheating temperature of 150°C.

[0051] The preheating temperature is 150℃, which is relatively lower, can save energy and avoid the derivative problems caused by excessive temperature.

[0052] Preferably, the second duration is 10 minutes.

[0053] Preheat at 150°C for 10 minutes. The sample temperature will not be too high after preheating.

[0054] Preferably, in step S3.2, when plasma arc spraying is adopted, the spraying voltage range is 45-50V, the spraying current range is 500-550A, and the main gas flow range is 2300-2800ml / min.

[0055] The spraying voltage and current are lower than the usual specifications to ensure that the working gas is converted into active particle flow to reduce the power and avoid the change of coating caused by excessive temperature of plasma flow. The main gas flow of 2300-2800ml / min ensures sufficient airflow to maintain a stable arc without blowing away the spray powder.

[0056] Preferably, in step S3.3, the sample is polarized in a polarizer with an oil bath temperature of 70°C.

[0057] The samples were planned using a polarizer. The oil bath temperature of 70°C was relatively low, which could effectively polarize the materials, improve their performance, and ensure safety.

[0058] Preferably, the third duration is 30 minutes.

[0059] The polarization time is 30 minutes, which can ensure the piezoelectric properties of the piezoelectric coating.

[0060] Preferably, in step S3.4, the sample is washed at least twice with anhydrous ethanol, with each washing lasting 5 minutes.

[0061] Using anhydrous ethanol to clean the sample multiple times can ensure that the sample surface is clean and free of foreign matter. The cleaning effect is observed with the naked eye to obtain an intervertebral fusion device with piezoelectricity, which is beneficial to preserving the structural integrity and ultimate piezoelectric properties of the composite material.

[0062] Preferably, in step S2, the first duration is 2 hours.

[0063] Heat treating the sample for 2 hours can ensure the acquisition of α+β crystal phase structure and improve the comprehensive performance of the sample.

[0064] Example 1 of a method for preparing an intervertebral fusion cage

[0065] The 3D model of the intervertebral fusion cage was designed using the 3D design software 3D one Plus, and the STL format model was exported. The STL format model was imported into the software on the 3D printer, and the printing layer thickness was set to 50um, the scanning spacing was 90um, and the scanning speed was 1600mm / s; the support structure was generated, the substrate was preheated to 200℃ before molding, and printing began after nitrogen was introduced. After printing, the support structure was removed with needle-nosed pliers, and the sample was heat treated in a heat treatment furnace at a temperature of 800℃.

[0066] The sample of the intervertebral fusion device was preheated in a vacuum environment at a temperature of 150°C for 10 minutes, a spraying voltage of 45V, a spraying current of 500A, and a main gas flow rate of 2300ml / min. Barium titanate ceramic powder was sprayed onto the sample using a plasma arc spraying process, and the sample was polarized in an oil bath at 70°C. After polarization, the sample was repeatedly cleaned with anhydrous ethanol until it was clean, thereby obtaining an intervertebral fusion device with piezoelectricity.

[0067] Example 2 of the method for preparing an intervertebral fusion cage

[0068] The 3D model of the intervertebral fusion cage was designed using the 3D design software 3D one Plus, and the STL format model was exported. The STL format model was imported into the software on the 3D printer, and the printing layer thickness was set to 50um, the scanning spacing was 90um, and the scanning speed was 1600mm / s. The support structure was automatically generated. The substrate was preheated to 200℃ before molding, and printing began after nitrogen was introduced. After printing, the support structure was removed with needle-nosed pliers, and the sample was heat treated in a heat treatment furnace at a temperature of 800℃.

[0069] The sample of the intervertebral fusion device was preheated in a vacuum environment at a temperature of 150°C for 10 minutes, a spraying voltage of 47V, a spraying current of 520A, and a main gas flow rate of 2400ml / min. Barium titanate ceramic powder was sprayed onto the sample using a plasma arc spraying process, and the sample was polarized in an oil bath at 70°C. After polarization, the sample was repeatedly cleaned with anhydrous ethanol until it was clean, thereby obtaining an intervertebral fusion device with piezoelectricity.

[0070] Example 3 of the method for preparing an intervertebral fusion cage

[0071] The 3D model of the intervertebral fusion cage was designed using the 3D design software 3D one Plus, and the STL format model was exported. The STL format model was imported into the software on the 3D printer, and the printing layer thickness was set to 50um, the scanning spacing was 90um, and the scanning speed was 1600mm / s. The support structure was automatically generated. The substrate was preheated to 200℃ before molding, and printing began after nitrogen was introduced. After printing, the support structure was removed with needle-nosed pliers, and the sample was heat treated in a heat treatment furnace at a temperature of 800℃.

[0072] The sample of the intervertebral fusion device was preheated in a vacuum environment at a temperature of 150°C for 10 minutes, a spraying voltage of 48V, a spraying current of 540A, and a main gas flow rate of 2600ml / min. Barium titanate ceramic powder was sprayed onto the sample using a plasma arc spraying process, and the sample was polarized in an oil bath at 70°C. After polarization, the sample was repeatedly cleaned with anhydrous ethanol until it was clean, thereby obtaining an intervertebral fusion device with piezoelectricity.

[0073] Example 4 of the method for preparing an intervertebral fusion cage

[0074] The 3D model of the intervertebral fusion cage was designed using the 3D design software 3D one Plus, and the STL format model was exported. The STL format model was imported into the software on the 3D printer, and the printing layer thickness was set to 50um, the scanning spacing was 90um, and the scanning speed was 1600mm / s. The support structure was automatically generated. The substrate was preheated to 200℃ before molding, and printing began after nitrogen was introduced. After printing, the support structure was removed with needle-nosed pliers, and the sample was heat treated in a heat treatment furnace at a temperature of 800℃.

[0075] The sample of the intervertebral fusion device was preheated in a vacuum environment at a temperature of 150°C for 10 minutes, a spraying voltage of 50V, a spraying current of 550A, and a main gas flow rate of 2800ml / min. Barium titanate ceramic powder was sprayed onto the sample using a plasma arc spraying process, and the sample was polarized in an oil bath at 70°C. After polarization, the sample was repeatedly cleaned with anhydrous ethanol until it was clean, thereby obtaining an intervertebral fusion device with piezoelectricity.

[0076] The present invention also provides a preferred embodiment of an intervertebral fusion device with piezoelectric properties on the surface, which is prepared by the preparation method of the intervertebral fusion device of any of the above technical solutions. Figures 2 to 4 As shown, the intervertebral fusion device with piezoelectric properties on the surface includes a rear support segment 1 and a plurality of front limbs 2 connected to the rear support segment 1, the inner wall of each front limb 2 has an internal thread segment 3 at one end away from the rear support segment 1, the outer wall of the front limb 2 has an external thread segment 4, and the surfaces of the rear support segment 1 and the front limb 2 are both provided with a piezoelectric coating. The internal thread segment 3 is used for threaded assembly of screws, and the piezoelectric coating makes the surface of the intervertebral fusion device have piezoelectric properties, which can promote the fusion of human vertebrae and prolong the intervertebral fusion time.

[0077] In this embodiment, there are four forelimbs 2, and the four forelimbs 2 are spaced apart to form a cylindrical structure. The rear support segment 1 is a cylindrical structure. The cylindrical shape has a small cross-sectional area, which can implement minimally invasive surgery, resulting in small wounds, fast recovery, and reduced pain for patients.

[0078] After the intervertebral fusion device with piezoelectric properties on the surface is implanted in the body, it does not need screws for fixation, and the threads on the surface of the fusion device can form a good bite effect with the vertebral tissue. The internal thread section 3 on the front limb 2 can be threaded with a screw, and the screw can radially open the end of the front limb 2 away from the rear support section 1 to a certain angle, forming an interlocking structure with the patient's vertebral body, and no additional screws are needed for fixation.

[0079] In summary, the embodiments of the present invention provide an intervertebral fusion device with piezoelectric properties on the surface and a preparation method thereof. The intervertebral fusion device sample is manufactured by a 3D printing process, and the molding is simple and can be customized according to the needs of different patients. After the sample is manufactured and molded, it is heat treated to obtain an α+β titanium alloy crystal phase structure, and the comprehensive performance of the sample is improved. A piezoelectric coating is formed on the surface of the sample, and the intervertebral fusion device has piezoelectric properties. The piezoelectric coating can stimulate tissue growth and repair, accelerate bone integration, and promote intervertebral fusion in the human body.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an intervertebral fusion cage, characterized in that: The following steps are involved: S1, a sample of an intervertebral fusion cage was printed using 3D printing technology, and the sample material was titanium alloy; S2, heat treating the sample in step S1, the heat treatment temperature is 800° C., and the heat treatment time is a first duration; S3, coating the piezoelectric ceramic powder on the surface of the sample to form a piezoelectric coating.

2. The method for preparing an intervertebral fusion cage according to claim 1, characterized in that: Step S3 includes: S3.1, preheating the sample in a vacuum environment, the preheating temperature is 130℃-170℃, and the preheating time is the second time length; S3.2, piezoelectric ceramic powder is sprayed onto the sample using a plasma arc spraying process; S3.3, polarizing the sample in an oil bath, the oil bath temperature range is 40°C-70°C, and the polarization time is the third duration; S3.4, clean the sample and obtain the intervertebral fusion cage.

3. The method for preparing an intervertebral fusion cage according to claim 2, characterized in that: In step S3.1, preheating is performed in a vacuum oven at a preheating temperature of 150°C.

4. The method for preparing an intervertebral fusion cage according to claim 3, characterized in that: The second duration is 10 minutes.

5. The method for preparing an intervertebral fusion cage according to claim 2, characterized in that: In step S3.2, when plasma arc spraying is adopted, the spraying voltage range is 45-50V, the spraying current range is 500-550A, and the main gas flow range is 2300-2800ml / min.

6. The method for preparing an intervertebral fusion cage according to claim 2, characterized in that: In step S3.3, the sample is polarized in a polarizer with an oil bath temperature of 70°C.

7. The method for preparing an intervertebral fusion cage according to claim 6, characterized in that: The third duration is 30 minutes.

8. The method for preparing an intervertebral fusion cage according to claim 2, characterized in that: In step S3.4, the sample is washed at least twice with anhydrous ethanol, each washing lasting 5 minutes.

9. The method for preparing an intervertebral fusion cage according to claim 1, characterized in that: In step S2, the first duration is 2 hours.

10. An intervertebral fusion device having a surface having piezoelectric properties, characterized in that: The intervertebral fusion device is prepared and molded by the preparation method of any one of claims 1 to 9, and the intervertebral fusion device with piezoelectric properties on the surface comprises a rear support segment, and a plurality of front limbs connected to the rear support segment, the inner wall of each of the front limbs has an internal thread segment at one end away from the rear support segment, the outer wall of the front limb has an external thread segment, and the surfaces of the rear support segment and the front limbs are both provided with a piezoelectric coating.

Citation Information

Cited By

  • Bionic interbody fusion cage with piezoelectric multifunctional coating

    CN122075195A

  • Biomimetic intervertebral fusion cage with piezoelectric multifunctional coating

    CN122075195B